Pengaruh Pendapatan Asli Daerah dan Distribusi Daerah Terhadap Belanja Daerah Di Kabupaten/Kota Sumatera Utara - Putri Cindi Claudia; Alistraja Dison Silalahi (ARBITRASE: Journal of Economics and Accounting, 2022)
The purpose of this study 1) To determine the effect of receipt of Local Own Revenue on increasing Regional Expenditure in the Regency/City of North Sumatra. 2) To determine the effect of receiving regional levies on increasing regional balances of North Sumatra Province. In this study the method of data analysis used by the author in analyzing the problems that exist in this study is to use quantitative methods. The type of data used in this study is secondary data, namely data in the form of figures contained in the APBD Realization report for districts/cities in North Sumatra for the 2018 to 2020 Fiscal Year and data related to research. From the results of this study it is known that Regional Own Revenue does not have a positive effect on regional spending while Regional Retribution has a positive effect on regional spending.